Literary culture in Taiwan : martial law to market law - Chang, Sung-sheng, 1951- (Columbia University Press, 2004)
Chang provides a comprehensive history of late 20th century Taiwanese literature by placing the vibrant local tradition within the contexts of a modernising economy, & a postcolonial, post-Cold War world order.